2014
DOI: 10.1371/journal.pone.0102224
|View full text |Cite|
|
Sign up to set email alerts
|

Using the Lives Saved Tool (LiST) to Model mHealth Impact on Neonatal Survival in Resource-Limited Settings

Abstract: While the importance of mHealth scale-up has been broadly emphasized in the mHealth community, it is necessary to guide scale up efforts and investment in ways to help achieve the mortality reduction targets set by global calls to action such as the Millennium Development Goals, not merely to expand programs. We used the Lives Saved Tool (LiST)–an evidence-based modeling software–to identify priority areas for maternal and neonatal health services, by formulating six individual and combined interventions scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 43 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…It is therefore crucial to inform decision-makers on the need to support the prioritization of interventions aimed at reduction of stunting and advocacy for increased funding of maternal and child survival interventions. There is already evidence that LiST identifies priority areas for child health investment based on modelling the impact of evidence-based interventions at varying levels of coverage [15][16][17][18]20]. Although LiST has been mainly used to model the impact of scaling up maternal, newborn and child health intervention on child mortality [15][16][17][18][19][20], in our study, we presented the impact of reducing the prevalence of stunting on child survival in a rural setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore crucial to inform decision-makers on the need to support the prioritization of interventions aimed at reduction of stunting and advocacy for increased funding of maternal and child survival interventions. There is already evidence that LiST identifies priority areas for child health investment based on modelling the impact of evidence-based interventions at varying levels of coverage [15][16][17][18]20]. Although LiST has been mainly used to model the impact of scaling up maternal, newborn and child health intervention on child mortality [15][16][17][18][19][20], in our study, we presented the impact of reducing the prevalence of stunting on child survival in a rural setting.…”
Section: Discussionmentioning
confidence: 99%
“…The Lives Saved Tool (LiST) [16][17][18][19][20] which is incorporated into the OneHealth software was used to estimate the impact of stunting reduction on child mortality and cases of stunting averted in two scenarios -a) halving the prevalence of stunting by 2040, b) zero stunted children in Buhweju district by 2040. The modelling period was set at 2017-2040 to align with the Uganda vision target of zero stunted growth by 2040 [7].…”
Section: Lives Saved and Number Of Cases Of Stunting Avertedmentioning
confidence: 99%
See 1 more Smart Citation
“…As a supplement to clinical care, mHealth has tremendous potential to benefit people in low- and middle-income countries (LMICs). Short-term studies have shown that mHealth can improve health and health systems, with many studies focused on the areas of reproductive, maternal, newborn and child health in LMICs [35]. Countless mHealth interventions have been developed to address the needs of LMICs, and even a cursory examination of medical databases reveals over 7500 scholarly articles related to mHealth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phones are thus changing the mode of communication globally and have proven a potential method of directly connecting pregnant women and mothers to health services [13]. SMS messages have also shown considerable impact on disease prevention efforts in developing countries and have particularly been quite effective for changing behavior in treatment adherence, smoke cessation, and health care appointment attendance [14][15][16][17][18][19][20].…”
Section: ]mentioning
confidence: 99%